2023
DOI: 10.1097/bsd.0000000000001430
|View full text |Cite
|
Sign up to set email alerts
|

Return to Driving Is Safe 6 Weeks After Anterior Cervical Surgery for Symptomatic Cervical Degenerative Disc Disease

Abstract: Objectives: This study aims to determine the timing and clinical parameters for a safe return to driving.Summary of Background Date: Returning to driving after cervical spine surgery remains a controversial topic, with no clear consensus on how to best assess a patient's fitness to drive. Previous studies using brake reaction time or subjective questionnaires recommend a return to driving 6 weeks after surgery. Methods: Patients above 18 years of age who underwent anterior cervical spine surgery for symptomati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Here, we found that most patients were able to return to driving with CDR patients returning to driving quicker. Ding et al 18 previously reported that at six weeks postoperatively, most patients pass a driving assessment. Our results indicate return may be even quicker.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we found that most patients were able to return to driving with CDR patients returning to driving quicker. Ding et al 18 previously reported that at six weeks postoperatively, most patients pass a driving assessment. Our results indicate return may be even quicker.…”
Section: Discussionmentioning
confidence: 99%